Fulmina illa Ciceronis: Atmospheric Phenomena in the Treatment of the genus grande - Benvenuti, Francesca (Wiener Studien, 2025)
This paper analyzes imagery of thunder and lightning-flashes in the description of speech in its powerful and grandiose effects and in the definition of a literary canon in Latin rhetoric. In particular, firstly used in Cicero's rhetorical works and letters on the basis of Greek models and in a clear polemic against the Atticists, the imagery allowed Cicero to place himself in competition with the Greek canon, after Pericles and especially Demosthenes, and at the forefront of the Roman literary tradition. In this respect, the imagery defines a literary canon that was variously adopted or rejected by subsequent rhetors and writers.